2013
DOI: 10.1161/circulationaha.113.001588
|View full text |Cite
|
Sign up to set email alerts
|

Treacher Collins Syndrome

Abstract: The online-only Data Supplement is available with this article at http://circ.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…TCOF1 is involved in mRNA formation in NCCs during embryogenesis, largely associated with NC depletions in pharyngeal arches 1 and 2 [69]. Treacher Collins is normally associated with craniofacial abnormalities, but the depletion of NCCs has also been indicated in producing human CHD phenotypes such as VSD, ASD, PDA [70]. Studies have found that haploinsufficiency of TCOF1 in mice results in a reduced number of migrating NCCs, leading to severe craniofacial defects [69].…”
Section: Treacher Collins Syndromementioning
confidence: 99%
“…TCOF1 is involved in mRNA formation in NCCs during embryogenesis, largely associated with NC depletions in pharyngeal arches 1 and 2 [69]. Treacher Collins is normally associated with craniofacial abnormalities, but the depletion of NCCs has also been indicated in producing human CHD phenotypes such as VSD, ASD, PDA [70]. Studies have found that haploinsufficiency of TCOF1 in mice results in a reduced number of migrating NCCs, leading to severe craniofacial defects [69].…”
Section: Treacher Collins Syndromementioning
confidence: 99%